Synchronization of Media Agendas between Social Media and Newspaper Websites: A Case Study of Inter Media Setting during AM and PM time Periods) - Abdul Rehman Qaisar (Journal of Peace, Development and Communication, 2021)
Present study comprised of Ante Meridiem (AM) vs Post Meridiem (PM) intermedia agenda-setting between newspapers’ websites and twitter. Data regarding Turkish President’s visit to Pakistan has been collected from a website of famous English newspaper “The Nation”. Data from Twitter has been collected using APIs. The finding shows that there is a significant synchronous correlation (X2Y2) between Twitter and selected newspapers (The Nation) during Post Meridian (PM) (r1= +0.472, r2= +0.841 and r3= +0.752). Reduced posting on Twitter and newspaper’ websites has been observed during the Ante Meridiem (AM) time period. Study has reported gradual content build-up on a simultaneous basis on Twitter and news websites during the PM time period. It also indicates increasing integration between social media and traditional media’s online spaces. Analysis of Twitter posts shows that there is a synchronization among contents of social media and traditional media’s online spaces as a vast majority of Twitter posts are based on clippings of newspapers stories or video footages from news channels. On the other hand, majority of anchors, reporters, columnists, independent journalists and writers are using Twitter to discuss and break exclusive news stories. Politicians are using Twitter as their major interaction facility for both media and public. In Pakistan tweets made by politician, military representatives, and famous media persons are flashed as breaking news on channels and the same is given coverage prominently on news-websites. It becomes a cyclic activity when these published news stories and footages become tweets as a matter of success and pride. The study has also observed consistent use of social media cells by political parties for pushing agendas on social media to get attention on other media outlets. Circular model for network journalism and simultaneous agenda setting has been proposed. Model elaborates how contents move in a circular way in network journalism environment. Keywords: Synchronization in Inter Media Agenda Setting, Circular Model for Network Journalism, AM vs PM Agenda Building and Transfer. Integrated Inter Media Agenda Setting, Simultaneous Agenda Setting